SAT0370 Antineutrophil Cytoplasmic Antibody (ANCA) Type and Body Mass Index in Anca-Associated Vasculitis. (15th July 2016) - Wallace, Z.; Specks, U.; Hoffman, G.; Kallenberg, C.; Langford, C.; Merkel, P.; Monach, P.; Seo, P.; Spiera, R.; Clair, B.St.; Choi, H.; Stone, J.
Abstract : Background: Recent studies have highlighted important phenotypic, genetic, and treatment differences between PR3- and MPO-ANCA+ ANCA-associated vasculitis (AAV) patients 1, 2 . No study has evaluated differences in body mass index (BMI) between the PR3- and MPO-ANCA+ AAV subtypes. Objectives: We sought to evaluate whether differences in BMI exist between patients with active PR3-ANCA+ and MPO-ANCA+ AAV using data from the Rituximab in ANCA-Associated Vasculitis (RAVE) trial 3 . Methods: We analyzed AAV patients who were either anti-proteinase 3 (PR3) antibody+ or anti-myeloperoxidase (MPO) antibody+ from the Rituximab in ANCA-Associated Vasculitis (RAVE) trial. In univariate analyses, we compared the BMI/weight of PR3- and MPO-ANCA+ AAV patients at enrollment, using linear regression to adjust for age, gender, glucocorticoids prior to enrollment, relapsing disease at baseline, and baseline disease activity. We used an analysis of response profile to evaluate trends in BMI and weight by ANCA type, adjusted for the above confounders as well as cumulative steroid dosing during the trial and flares during the trial. Results: Three fourths of the patients were PR3+ (147, 75%). PR3-ANCA+ patients had a higher BMI at baseline compared to MPO-ANCA+ patients (29.6±6.6 vs. 27.2 ± 5.3; P=0.01); the same was true for weight differences (89.3 ±22kg vs. 77.2 ± 16.0kg, respectively, P<0.001). A significantly greater proportion of PR3-ANCA+ patients (42%) were obese compared to MPO-ANCA+ patients (24%, P=0.04). Among those with a new diagnosis of AAV at enrollment (N=96), PR3-ANCA+ patients had a significantly higher BMI (29.2 ± 6.2) compared to MPO-ANCA+ patients (26.8 ± 4.9, P=0.04). In multivariate linear regression analyses, these differences (PR3-ANCA + BMI 2.1 kg/m 2 (±1.1) higher than MPO-ANCA+ patients) remained significant (P=0.047 for BMI and 0.04 for weight, respectively) after accounting for confounders. The difference in weight between PR3-ANCA+ and MPO-ANCA+ patients remained stable during the study (P=0.3). Conclusions: PR3-ANCA+ patients have a significantly higher BMI than MPO-ANCA+ patients, even after adjustment for important potential confounders. Our findings may have important implications for our understanding of AAV pathogenesis, its relationship to metabolic pathways, and the management of AAV. References: Rahmattulla C, Mooyaart AL, van Hooven D, et al. Genetic variants in ANCA-associated vasculitis: A meta-analysis. Ann Rheum Dis. 2015. doi: 10.1136/annrheumdis-2015-207601. Hilhorst M, van Paassen P, Tervaert JW, Limburg Renal Registry. Proteinase 3-ANCA vasculitis versus myeloperoxidase-ANCA vasculitis. J Am Soc Nephrol. 2015;26(10):2314–2327. Stone JH, Merkel PA, Spiera R, et al. Rituximab versus cyclophosphamide for ANCA-associated vasculitis. N Engl J Med. 2010;363(3):221–232. Disclosure of Interest: None declared